Continuous teacher education process in school - Abdul Majid Halimah, Chuah Beng Ean, Eow Yee Leng, (Universiti Pendidikan Sultan Idris, 2016)
Continuous teacher education process in school by Abdul Majid Halimah, Chuah Beng Ean, Eow Yee Leng,